Microwave assisted synthesis, characterization and antimicrobial screening of drug based schiff base silver complexes - SHILPA KODGE; K. H. SHIVPRASAD; VIJAYAKUMAR DURG; ANILKUMAR KODGE (International Journal of Pharma and Bio Sciences, 2017)
A series of drug based Schiff base ligands and their silver complexes were synthesized in alcoholic medium by microwave irradiation. The method yielded ligands and complexes in good quantities. The microwave synthesis has been found to be, relatively, simple and easier to carry out. The ligands and their silver complexes were characterized by elemental analysis, IR and NMR spectral data. The complexes were tested for antifungal and antibacterial activity. They have shown very good inhibition for fungal pathogens (C. albicans and Aspergillus niger) and pathogenic bacteria (S. aureus and E. coli).